Internasionalisme Islam pada Kasus Konfrontasi Iran-Israel dalam Perspektif Siyasah Dauliyah - Satryo Pringgo Sejati; Hakim , Ahmad Burhan (JOSH: Journal of Sharia, 2025)
The confrontation that occurred between Iran and Israel is certainly interesting to discuss academically. Because so far indirectly there has not been a single country in the East-Middle East region that has the courage and ability to fight Israel. Iran today appears as an Islamic state that dares to resist Israel's oppression. As for the problems that occur in Palestine, vis-à-vis it is not balanced if Palestine fights Israel because many of the Israeli histories are directly related to Palestinian civilians, so it is certainly not balanced. Now June 2025 will be a new historical witness that Iran is clearly brave and capable of brutally attacking Israel by launching many missiles in the Tel Aviv area and its surroundings, which many western media claim that the city can almost penetrate with modern missiles. In fact, missiles from Iran were able to penetrate Israeli defenses and Tel Aviv finally conceded and were destroyed. After this incident, Islamic internationalism and support for Iran emerged from many Middle Eastern countries, except for countries that are indeed allied with the United States. Islamic internationalism emerged and became a moral force for Iran to continue to be able to confront Israel.  The research method used in this article is an explanatory qualitative research method, using primary data and secondary data according to the needs of this study. Literature studies are also used to conduct research on the listeration that is needed. Islamic internationalism has existed for a long time, but it has also been buried and sunk for a long time. The moment of Iran's rise to be able to fight Israel is an important moment in the rise of Islamic Internationalism in the perspective of siyasah dauliyah.